Imaging and analysis of single atoms and molecules by transmission electron microscopy - Cardillo-Zallo, Ian T. B. (2025)
The transmission electron microscope (TEM) is a powerful tool that can resolve the positions of individual atoms within a material. Measurement of the position and motion of single atoms via TEM imaging and spectroscopy provides understanding of how matter behaves at the fundamental level, without relying on bulk measurements averaged over many particles. Further, the high energy electron beam can initiate chemical transformations within the microscope, which can be imaged in real time with high spatial resolution.